2022
DOI: 10.3389/fphys.2022.874015
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Stiffness in L-NAME Treated C57Bl/6 Mice Displays a Shift From Early Endothelial Dysfunction to Late-Term Vascular Smooth Muscle Cell Dysfunction

Abstract: Introduction and Aims: Endothelial dysfunction is recognized as a cardiovascular aging hallmark. Administration of nitric oxide synthase blocker N-Ω-Nitro-L-arginine methyl ester hydrochloride (L-NAME) constitutes a well-known small animal model of cardiovascular aging. Despite extensive phenotypic characterization, the exact aortic function changes in L-NAME treated mice are largely unknown. Therefore, this study presents a longitudinal characterization of the aortic reactivity and biomechanical alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…These data are in line with consensus scientific literature. Impaired endothelial relaxation is involved in blood pressure (Betrie et al, 2021 ; Panza et al, 1990 ; Perticone et al, 2001 ) and aortic stiffness (De Moudt et al, 2022a , c ; Leloup et al, 2018 ) dysregulation, and is a known risk factor for cardiovascular disease (Rajendran et al, 2013 ). Mollnau et al ( 2002 ) showed that AngII infusion decreased NO production in the aorta of Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in line with consensus scientific literature. Impaired endothelial relaxation is involved in blood pressure (Betrie et al, 2021 ; Panza et al, 1990 ; Perticone et al, 2001 ) and aortic stiffness (De Moudt et al, 2022a , c ; Leloup et al, 2018 ) dysregulation, and is a known risk factor for cardiovascular disease (Rajendran et al, 2013 ). Mollnau et al ( 2002 ) showed that AngII infusion decreased NO production in the aorta of Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Low muscle mass also increased cardiovascular risk and all-cause mortality (9,(13)(14)(15). Decreased skeletal muscle mass is related to arterial stiffness, which precedes the development of hypertension (16) in young adults and patients with diabetes (17,18). In addition, skeletal muscle has an endocrine function by secreting several myokines (19) and dysregulated crosstalk leads to, or confounds energy and fluid homeostasis (20)(21)(22), which might result in hypertension.…”
Section: Introductionmentioning
confidence: 99%